Lead poisoning from Ayurvedic treatment: a further case.: Medicina alternativa e rischi per la salute - Ciocan, Catalina; Mansour, Ihab; Beneduce, Alessandro; Corgiat Loia, Riccardo; Milanesio, Nicolò; Declementi, Michael; Godono, Alessandro; Garzaro, Giacomo; Pira, Enrico (La Medicina del Lavoro, 2021)
Purpose: We report a case of a 30 years old Indian sailor with microcytic anemia (Hb 9.9), persistent abdominal pain, emesis, dark stool, hyperchromic urine, latent jaundice and asthenia. Lead intoxication was confirmed (blood lead value of 102 μg/dL). The patient assumed Ayurvedic medicines in the previous months. Ayurveda is an ancient form of Indian traditional popular medicine aiming to re-establish health and body function through herbal preparations, heavy metals are often added. Our purpose was to treat the patient and to establish the source of poisoning. Methods: After testing blood and urine lead concentration of other 3 crew members and analyzing over than 150 products used on the ship professional exposure was excluded. We analyzed the two Ayurvedic drugs assumed by the patient with an Inductively Coupled Plasma Mass Spectrometry. The patient underwent three chelation cycles with Calcium Disodium Ethylenediaminetetraacetic acid (EDTA) while monitoring blood and urinary lead levels. Results: The final blood lead level at discharge, after three chelation cycles, was 36.27 μg/dL. One of the two drugs contained extremely high concentrations of lead and mercury. The three different mixtures of this preparation showed lead concentrations of 12,638.54 mg/kg (Sample 2A), 23,043.02 mg/kg (Sample 2B), 21,352.97 mg/kg (Sample 2C); these levels are much higher than the highest values reported in literature for the indian soil (32 mg/kg). Conclusions: This case and similar cases raise the safety alert on complementary and alternative medicines; Ayurvedic medicine users should be carefully informed about potential risks and signs of poisoning.